IMPROVING FOREHAND STRIKES IN FIELD TENNIS GAMES THROUGH THE DRILL METHOD IN SCHOOLS - Ilham Azis; Muhammad Qasash Hasyim (Adisam Publisher, 2024)
This article addresses key aspects such as body position, hip rotation, and core strength with physical and mental exercises that contribute to stronger punches and hitting accuracy. Through implementing these strategies, players can develop more effective shots and improve their ability to control and dominate the court. Combining the right technique and training will be the key to achieving superior hitting power in tennis. Court tennis forehand technical skills include open skills. Open skills are movement skills where the implementation occurs in changing environmental conditions, and the actor moves according to the stimulus that arises. Temporal and special changes in environmental conditions will stimulate students to move. When students perform forehand movements, they will adjust the incoming ball so that they can adjust the position of their feet, bet and starting point in executing their forehand. The drill method for forehand strokes is a movement that is done with a sprint movement to move forward or obliquely forward, a step to the right, left side, and a backward movement to move backwards and obliquely backwards. Thus, if training using the drill method is carried out seriously and according to instructions, it will be able to improve your forehand ability to become better, so that during games or matches it will be an advantage for scoring points.